Promotion Strategy PF PE Training Service in Guangzhou-Taking the Consumption Behavior and Utilization Rate of Large Public Stadiums as an Example - Riqiang, Zhong; Satchanan, Siriporn; Chantanasiri, Supattra; Kositkanin, Thananwarin (วารสารนวัตกรรมการจัดการศึกษาและการวิจัย, 2023)
The aims of this research were to 1. analyze the driving factors and mechanism of urban residents’ sports venue consumption behavior. 2. analyze the main game relationship between the government, stadiums, and urban residents 3. Analyze the impact of the size on the evolution path of the system and the impact of the size of the government’s negligence loss on the evolution path of the system influence the behavior evolution path of three important adjustment parameters. Qualitative Research: The sample selection of interviewees was 30 respondents from Beijing, Shanghai, and Guangzhou. Quantitative Research was used by China's professionals by stratified random sampling of the field survey of 1,274 questionnaires. The findings: 1. the analyzed driving factor and mechanism of urban residents’ sports venue consumption behavior indicated the residents adopt two behavioral strategies: "exercise in the stadium" and "exercise in the gymnasium". 2. the analysis of the main game relationship between the government, stadiums, and urban residents indicated (1) the behavior of stadiums and gymnasiums and (2) the behavior in sports venues above that subjective. (3) the analysis of the predictive effect of psychological factors on the overall interpersonal consumption behavior in stadiums and gymnasiums at the statistically significant level of .01. And 3. the analysis of impact of the size on the evolution path of the system and the impact of the size of the government’s negligence loss on the evolution path of the system influence the behavior evolution path of three important adjustment parameters indicated a theoretical model of the impact mechanism of the consumption behavior of urban residents' stadiums and gymnasiums.